Pengembangan Prodi Manajemen Pendidikan Kristen: Sebuah Studi Kasus - Lasmaria Lumban Tobing; Nasib Tua Lumban Gaol; Rogate Gultom; Marudut Situmorang; Robert Juni Tua Sitio (Sekolah Tinggi Teologi Simpson Ungaran, 2021)
Since its establishment in 2018, Christian education management has begun to develop continuously in the educational context of Indonesia. However, it still requires studying more. Accordingly, this research aims to investigate how the department of Christian education management may be developed at the Christian higher education. The qualitative research, in particular, a case study was conducted to investigate the topic. Seven participants were involved and a manual book of Christian educational management department was used as the source of data. Based on the result of the study, it was found four themes that need to pay attention seriously in order to develop further the department of Christian educational management in Christian higher education, namely vision, mission, purpose, curriculum, collaboration, and alumnus. On the other side, for improving the knowledge on the management of Christian education organizations, contributions of this study for further research, practitioners and policy-makers are providedÂ